Factors affecting survival after liver retransplantation: a systematic review and meta-analysis - Brombosz, Elizabeth W.; Moore, Linda W.; Mobley, Constance M.; Kodali, Sudha; Saharia, Ashish; Hobeika, Mark J.; Connor, Ashton A.; Victor, David W.; Cheah, Yee Lee; Simon, Caroline J.; Gaber, Ahmed Osama; Ghobrial, Rafik Mark (Frontiers in Transplantation, 2023)
Background: Liver retransplantation (reLT) has historically had inferior survival relative to primary liver transplant (LT). To improve outcomes after reLT, researchers have identified factors predicting overall (OS) and/or graft survival (GS) after reLT. This systematic review and random effects meta-analysis sought to summarize this literature to elucidate the strongest independent predictors of post-reLT. Methods: A systematic review was conducted to identify manuscripts reporting factors affecting survival in multivariable Cox proportional hazards analyses. Papers with overlapping cohorts were excluded. Results: All 25 included studies were retrospective, and 15 (60%) were single-center studies. Patients on pre-transplant ventilation (HR, 3.11; 95% CI, 1.56-6.20; p=0.001) and with high serum creatinine (HR, 1.46; 95% CI, 1.15-1.87; p=0.002) had the highest mortality risk after reLT. Recipient age, Model for End-Stage Liver Disease score, donor age, and cold ischemia time >12 h also conferred a significant risk of post-reLT death (all p<0.05). Factors affecting GS included donor age and retransplant interval (the time between LT and reLT; both p<0.05). OS is significantly higher when the retransplant interval is ≤7 d relative to 8-30 days (p=0.04). Conclusions: The meta-analysis was complicated by papers utilizing non-standardized cut-off values to group variables, which made between-study comparisons difficult. However, it did identify 7 variables that significantly impact survival after reLT, which could stimulate future research into improving post-reLT outcomes.